Influence of post-flood impacts on farmers’ social adaptation level in Kelantan, Malaysia - Zahari, Mohd Hazran (2018)
Agriculture greatly depends on climate. The climate change affects the environment condition for agriculture. Agriculture in Malaysia is not free from natural disaster especially flood. Floods disrupted agriculture community such as social, economic and environment. Kelantan state was hit by flood at the end of 2014 and affected most of Kelantan agriculture land. The flood consequently reduces agriculture production. To decrease the risks of social and economic impacts, there is a need for long-term adaptive strategies especially in agriculture community. Adaptability of community on climate change had limited capacity due to vulnerability of their locations, socioeconomic, demographic and policy on climate change. Agriculture community attitude had influenced by education, experience, family size and income that had played significant role towards post flood impacts. Thus, long-term adaptive strategies in agriculture and farmers’ adaptive capacity need to be discover as preparation for future natural disaster event. These days, Malaysia lacks of research on social adaptation of farmers community in Malaysia. The general objective this study is to identify the influence of post-flood impacts to social adaptation of farmers in Kelantan. The specific objectives of this study are: 1) to evaluate the post-flood impacts level on respondents’ socio economy, agriculture activities, environment, emotion and psychology and food security; 2) to identify the respondents’ level of social adaptation; 3) to investigate the relationship between socio-demographic factors and respondents’ level of social adaptation; 4) to determine the relationship between the post-flood impacts level of respondents with level of social adaptation; and 5) to develop social adaptation index as indicator of farmers’ social adaptation in Kelantan. The data of this study collected through the survey of 371 farmers that were 2014 flood victims in Kelantan. Questionnaires were set up to achieved objectives of this study. Descriptive statistic results showed that most of the respondents’ age is between 51- 60 years old. Majority of respondents’ experience in agriculture is more than 16 years. Majority of respondents earned monthly income below RM1000. Most of respondents are not received any helps and aids to restart their farms. In aspects of damages and impacts, most of the respondents perceived that their emotion and psychology and livestock or crop were the most affected. This study identified that there is no significant relationship between five (5) factors affected by post-flood impact: 1) agriculture activities; 2) socioeconomics; 3) environment; 4) emotion and psychology; and 5) local food security with the level of respondents’ social adaptation. However, there were significant associations between socio demographic of respondents (age, education level and main occupation, per monthly income, type of subsector and cost of damage percentage estimation) with respondents’ social adaptation level. The finding revealed that their social adaptation index is moderate level. This study concluded that the social adaptation index level of respondents in Kelantan were moderate due to the respondents were partially resilient with the fluctuation of climate change in their places however to some region, the respondents did not affect with the flood event. Thus, this study recommended that there is a critical need to strengthen the social adaptation of farmers towards flood impacts and climate change. The strategies are encouraging the farmers to practice good preparation operation such as preparation to free livestock during flood and have a proper storage that resists from flood to reduce the impact. Other than that, extension program and activities could help the farmers to redevelop their farms again after the flood. Besides, agriculture institutes should introduce alternative crops that could regenerate income temporarily before restore their own farming.